2015
DOI: 10.1016/j.jcrs.2014.04.038
|View full text |Cite
|
Sign up to set email alerts
|

Anterior chamber depth measurements using Scheimpflug imaging and optical coherence tomography: Repeatability, reproducibility, and agreement

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
2
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 30 publications
4
27
2
1
Order By: Relevance
“…[14] Aramberi et al and Wang et al also showed a good level of agreement between the two Scheimpflug devices in AC depth measurements. [1015] The results of the current study similarly showed a significant correlation between Pentacam and Galilei with respect to the AC depth. In contrast with our findings, Anayol et al found a significant difference in AC depth values obtained by the Galilei, Pentacam, and Sirius.…”
Section: Discussionsupporting
confidence: 74%
“…[14] Aramberi et al and Wang et al also showed a good level of agreement between the two Scheimpflug devices in AC depth measurements. [1015] The results of the current study similarly showed a significant correlation between Pentacam and Galilei with respect to the AC depth. In contrast with our findings, Anayol et al found a significant difference in AC depth values obtained by the Galilei, Pentacam, and Sirius.…”
Section: Discussionsupporting
confidence: 74%
“…Some studies have assessed the repeatability of various anterior segment measurements provided by the same Scheimpflug imaging-based system as that used in the current study [6][7][8][9][10], with most reporting high levels of consistency [10][11][12][13][14]. However, few works have studied the repeatability of IA measurements [8], and to date, there is no study validating the consistency of measurements provided by the glaucoma mode of the Scheimpflug imagingbased system used in our series.…”
Section: Discussionmentioning
confidence: 99%
“…One example of a system providing non-invasive measurement of the IA is the Sirius ® system (Costruzione Strumenti Oftalmici [CSO], Florence, Italy), a non-contact 3D rotating Scheimpflug camera combined with a Placido ring that provides different anatomical measurements of the anterior segment. While there is strong scientific evidence of the consistency and repeatability of anterior segment measurements provided by this system in healthy and even pathological eyes [6][7][8][9][10][11][12][13][14][15], evidence of the repeatability of IA measurements is limited [8]. Likewise, to the best of our knowledge, no studies have evaluated and compared the consistency of IA measurements at different nasal and temporal meridians using this device.…”
Section: Introductionmentioning
confidence: 99%
“…Los participantes de dichos estudios se clasificaron por medio de la gonioscopía, inicialmente en dos grupos de muestra, un grupo de sujetos con ángulo cerrado y un segundo grupo de sujetos con ángulo abierto, con un rango de edad que se encontraba entre los 30 y los 83 años y con un promedio de edad o medianas entre los 51 y los 67 años, haciéndose necesario examinar sujetos de edades más avanzadas para obtener los dos grupos de muestra necesarios (11,13,16,18,20). En cambio, en el presente estudio se encontró similitud de las edades de los sujetos con respecto a las investigaciones donde no se hace una clasificación previa de los pacientes con ángulo de la cámara anterior cerrada o abierta, estudios que comprendían sujetos con edades promedio o medianas, entre los 30 y los 36 años (9,15,21,22).…”
Section: Discussionunclassified